The Human Dive Reflex During Consecutive Apnoeas in Dry and Immersive Environments: Magnitude and Synchronicity - Nordine, Michael; Schwarz, Anton; Bruckstein, Renana; Gunga, Hanns-Christian; Opatz, Oliver (Frontiers in Physiology, 2022)
Introduction: The human dive reflex (HDR), an O2 conserving reflex, is characterised by an interplay of central parasympathetic and peripheral sympathetic reactions, which are presumed to operate independently of each other. The HDR is fully activated during apnoea with facial immersion in water and complete immersion in water is thought to increase the magnitude of HDR during consecutive apnoeas. A comparison of HDR activity between consecutive apnoeas in full-body immersion with consecutive apnoeas in dry conditions has not been fully explored. Also, the interplay between parasympathetic and sympathetic reactions involved in the HDR has not been thoroughly analysed. Methods: 11 human volunteers performed 3 consecutive 60 s apnoeas with facial immersion in dry conditions (FIDC) and 3 consecutive apnoeas with facial immersion in full immersion (FIFI). Heart rate (HR), R-R interval (RRI), finger pulse amplitude (FPA), splenic width (SW) and SpO2 were all measured before, during and after apnoeas. A one-way ANOVA using Dunn’s post hoc test was performed to assess HDR activity, and a Pearson’s correlation test was performed to assess HDR synchronisation between physiological parameters during both conditions. Results: Although HDR activity was not significantly different between both conditions, HR and RRI showed progressively greater changes during FIFI compared with FIDC, while SW and FPA changes were relatively equivalent. During FIDC, significant correlations were found between SW & SpO2 and FPA & SpO2. During FIFI, significant correlations were found between RRI & FPA, SW & FPA, HR & SpO2 and FPA & SpO2. Discussion: While there was no significant difference found between HDR activity during FIDC and FIFI, consecutive apnoeas during FIFI triggered a greater magnitude of cardiac activity. Furthermore, significant correlations between RRI and SW with FPA indicate a crosstalk between parasympathetic tone with splenic contraction and increased peripheral sympathetic outflow during FIFI compared to FIDC. In conclusion, HDR activity during consecutive apnoeas does not differ between FIDC and FIFI. There appears to be however a greater level of synchronicity during apnoeas in FIFI compared to FIDC and that this is most likely due to the physiological effects of immersion, which could induce neural recruitment and increased cross talk of HDR pathways.